The opinion of Turkish cardiologists on current malpractice system and an alternative patient compensation system proposal: PCS study group - Olcay, Ayhan; Emren, Sadık Volkan; Güler, Gamze Babür; Güler, Ekrem; Ertunç, Vedat; Berilgen, Rida; Aslan, Abdullah; Şimşek, Ersin Çağrı; Gölcük, Şükriye Ebru; Yalın, Kıvanç (Turkish Society of Cardiology, 2017)
Objective: Cardiologists participate in the diagnosis and interventional treatment of numerous high-risk patients. The goal of this study was to investigate how the current malpractice system in Turkey influences cardiologists' diagnostic and interventional behavior and to obtain their opinions about an alternative patient compensation system. Methods: The present cross-sectional study assessed the practice of defensive medicine among cardiologists who are actively working in various types of workplace within the Turkish healthcare system. A 24-item questionnaire was distributed to cardiology residents, specialists, and academics in Turkey in print format, by electronic mail, or via cell phone message. Results: A total of 253 cardiologists responded to the survey. Among them, 29 (11.6%) had been sued for malpractice claims in the past. Of the cardiologists who had been sued, 2 (6.9%) had been ordered to pay financial compensation, and 1 (3.4%) was given a sentence of imprisonment due to negligence. In all, 132 (52.8%) of the surveyed cardiologists reported that they had changed their practices due to fear of litigation, and 232 (92.8%) reported that they would prefer the new proposed patient compensation system to the current malpractice system. Among the cardiologists surveyed, 78.8% indicated that malpractice fear had affected their decision-making with regard to requesting computed tomography angiography or thallium scintigraphy, 71.6% for coronary angiography, 20% for stent implantation, and 83.2% for avoiding treating high-risk patients. Conclusion: The results of this survey demonstrated that cardiologists may request unnecessary tests and perform unneeded interventions due to the fear of malpractice litigation fear. Many also avoid high-risk patients and interventions. The majority indicated that they would prefer the proposed alternative patient compensation system to the current malpractice system.

Amaç: Kardiyologlar birçok riskli hastanın teşhis, tedavi ve girişimsel tedavisiyle uğraşmaktadırlar. Bu çalışmada Türkiye’deki mevcut “malpraktis” sisteminin kardiyologların tanı ve tedavi yaklaşımlarını nasıl etkilediğini ve önerdiğimiz yeni hasta tazminat sistemine yaklaşımlarını inceledik. Yöntemler: Bu kesitsel çalışmada Türk sağlık sisteminin farklı seviyelerinde çalışan kardiyologların mesleki risk algılarının uygulamalarına etkisini araştırma amacıyla 24 soruluk bir anketi asistan, uzman ve öğretim üyelerine elektronik posta, basılı evrak ve cep telefonu mesajı ile gönderildi. Bulgular: Ankete toplam 253 kardiyolog cevap verdi. Bunların 29’una (%11.6) geçmişte malpraktis talepleri için dava açılmıştı. Dava edilen kardiyologların 2’sine (%6.9) maddi tazminat talebinde bulunuldu, 1’ine (%3.4) ihmal nedeniyle hapis cezası verildi. Bunun yanında 132 (%52.8) kardiyolog “malpraktis” korkusu nedeni ile pratiklerinde değişiklik yaptıklarını bildirmekteydi. Ayrıca 232 (%92.8) kardiyolog önerdiğimiz hasta tazminat sistemini tercihe değer buluyordu. Kardiyologların %78.8’i bilgisayarlı tomografik anjiyografi (BTA) veya perfüzyon sintigrafisi, %71.6’sı koroner anjiyografi, %20 ’si stent implantasyonu, %83.2’si ise yüksek riskli hastalardan kaçınma kararlarında malpraktisten kaçınmanın etkili olduğu kanaatindeydi. Sonuç: “Malpraktis” korkusu kardiyologlarda yüksek oranlarda gereksiz test isteme, girişim yapma veya yüksek riskli hastalardan kaçınma eğilimi yaratmaktadır. Önerdiğimiz yeni “malpraktis” sistemi çalışmaya katılan kardiyologların büyük çoğunluğu tarafından mevcut sisteme tercih edilir bulunmuştur.
Türkiye’deki kardiyologların mevcut “malpraktis” sistemi ve alternatif “malpraktis” sistem önerisi hakkındaki görüşleri
WOS: 000418480800009
PubMed ID: 28990944
Keywords: Cardiology; Defensive Medicine; Malpractice; Patient Compensation System; Hasta Tazminat Sistemi; Kardiyoloji; Defansif Tıp; Malpraktis